2020
DOI: 10.1007/s00431-020-03683-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of COVID-19 infection in pediatric patients: early findings from two Italian Pediatric Research Networks

Abstract: Detailed data on clinical presentations and outcomes of children with COVID-19 in Europe are still lacking. In this descriptive study, we report on 130 children with confirmed COVID-19 diagnosed by 28 centers (mostly hospitals), in 10 regions in Italy, during the first months of the pandemic. Among these, 67 (51.5%) had a relative with COVID-19 while 34 (26.2%) had comorbidities, with the most frequent being respiratory, cardiac, or neuromuscular chronic diseases. Overall, 98 (75.4%) had an asymptomatic or mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
151
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(182 citation statements)
references
References 12 publications
20
151
2
9
Order By: Relevance
“…Indeed, being our hospital qualified as COVID-19 hospital, our ED was efficiently reorganized to avoid intrahospital spread of SARS-CoV-2, separating suspected COVID-19 and standard care pathways. We detected only 1 case positive to SARS-CoV-2 (a 1.9-year-old girl admitted for complex febrile seizure) among 68 symptomatic and 47 asymptomatic patients tested with nasopharyngeal swab, confirming the low prevalence of COVID-19 among children and adolescents reported by other Italian records [7,8,17,27]. Febrile seizures represent a rare presentation of COVID-19 in pediatric age.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, being our hospital qualified as COVID-19 hospital, our ED was efficiently reorganized to avoid intrahospital spread of SARS-CoV-2, separating suspected COVID-19 and standard care pathways. We detected only 1 case positive to SARS-CoV-2 (a 1.9-year-old girl admitted for complex febrile seizure) among 68 symptomatic and 47 asymptomatic patients tested with nasopharyngeal swab, confirming the low prevalence of COVID-19 among children and adolescents reported by other Italian records [7,8,17,27]. Febrile seizures represent a rare presentation of COVID-19 in pediatric age.…”
Section: Discussionsupporting
confidence: 81%
“…Published preliminary Italian data confirmed a general favorable clinical course of COVID-19 in pediatric age [7]. However, two Italian Pediatric Research Networks reported a not negligible rate of severe presentations in children with comorbidities [8]; four deaths (age ≤ 9 years) have been reported on June 28th [9].…”
Section: Introductionmentioning
confidence: 98%
“…[10][11][12] Indeed, the population had become quickly aware that respiratory symptoms and fever could be warning signs for possible COVID-19, thus prompting caregivers to seek PED consultation for their children, despite the opposite recommendation by the national health service to stay at home and the low involvement of the paediatric age. [13][14][15][16] Conversely, PED visits for gastroenteritis showed a signi cantly fall in the COVID-19 period, probably because gastrointestinal symptoms were not known yet as a possible manifestation of COVID-19 by caregivers, particularly in the rst weeks of the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“… a lower frequency of infection [ 1 ], [ 2 ], [ 3 ], [ 4 ], [ 5 ] (some, but by far not all studies were conducted during the lockdown, which is a methodological limitation); a lower average severity of disease and associated with this; a significantly lower risk of the most serious, including fatal, courses; from CoVID-19 [ 6 ], [ 7 ], [ 8 ], [ 9 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ], [ 22 ], [ 23 ], [ 24 ]. …”
Section: Introductionmentioning
confidence: 99%